Innocent Victims In The Global War On Terror - Salloomi, M. A. (Mohammed A.) (Central Milton Keynes : AuthorHouse, 2011)
"The book presents a case that caused abundant arguments between the West & Islam after 09/11/2001. They are the allegations against a lot of the Charity and Humanitarian Organizations which had been accused for supporting Terrorism. Never-the-less [sic] the book replies scientifically to the big question, Does the Islam and it's organizations are new enemies [sic]? Strugglers and wrestler? or competitors. 09/11 had put on the track a new enemy, which led to designation of administrative arrangements, legal measures and political view points that are hardly changeable or can get rid of their legality, even under the changing governmental official-administration. Consequently the unemployment, the poverty and the diseases had increased so much. Most of people and minorities, countries, liberties and the civil rights became innocent victims to an endless war and undetermined delusive enemy and eventually slaughtered the peace-pigeons"--Amazon.com
The new competitors and the shift of power -- The rise of Non-Governmental Organizations (NGOs) -- The new competitors and the shift of power -- Bringing relief organizations under control -- The United Nations and the fourth World War -- Future outlook for the third sector -- Islamic charitable work: principles and means -- Participation of Islamic organizations in global efforts -- Examples of relief and development programs -- The value of the Islamic organizations within the international community -- The campaign against Islamic charities after 9/11 -- Propaganda war -- Campaign against Islamic organizations taking root before 9/11 -- Examples of the campaign -- America's sweeping demands -- The text of America's demands (Kuwait as an example) -- American measures that penalize everyone -- Islamic charities in the US Congress -- Hearing testimonies before the U.S. Congressional committees -- Does the case study offer any clue about the real objective? -- Does the religious foundation in Saudi Arabia offer any clue about the real objective? -- Report of the religious freedoms in the world: flawed OFAC (Designation criteria of the American justice) -- The declared objective of the campaign: analysis -- The new financial procedures and the declared objectives -- The British investigations of Islamic charities -- The Islamic charities in Bosnia -- Case studies Islamic charities under American hegemony -- Introduction to the case studies -- Case study 1. Palestine -- Case study 2. Afghanistan: the first victim -- Case study 3. Iraq: motives and objectives -- Mistakes of Islamic and non-Islamic organizations: a double standard -- Islamic organizations: mistakes, real and alleged -- Transgressions of some non-Islamic organizations -- The motives and objectives -- Indications and results that point to the real motives -- Islam and the West: competition or confrontation? -- Islam and the West: competition and conflict -- Conclusions -- Appendix -- Letters to the U.S. Congress / Friends of Charities Association (FOCA) members -- Open letter to the members of the U.S. Congress, April 4, 2006 / Friends of Charities Association (FOCA) members -- The list of the first group of persons and institutions quitted by the Federal Court
Includes bibliographical references (pages 313-336) and index
1
Keywords: War on Terrorism, -- 2001-2009